2016
DOI: 10.4103/0019-5413.173508
|View full text |Cite
|
Sign up to set email alerts
|

The best location for proximal locking screw for femur interlocking nailing: A biomechanical study

Abstract: Background:Proximal locking screw deformation and screw fracture is a frequently seen problem for femur interlocking nailing that affects fracture healing. We realized that there is lack of literature for the right level for the proximal locking screw. We investigated the difference of locking screw bending resistance between the application of screws on different proximal femoral levels.Materials and Methods:We used a total of 80 proximal locking screws for eight groups, 10 screws for each group. Three-point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The same experimental design was used by many researches with polyethylene tube [7][8][9], aluminium tube [13] -12] to obtain yield strength and yield point. With the polyethylene tube and aluminium tube to obtain true yield point was not likely as it was unreliable if the deformation that appears on the stress-strain graph belonged to polyethylene tube and its holes deformations or the locking screw deformation itself [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The same experimental design was used by many researches with polyethylene tube [7][8][9], aluminium tube [13] -12] to obtain yield strength and yield point. With the polyethylene tube and aluminium tube to obtain true yield point was not likely as it was unreliable if the deformation that appears on the stress-strain graph belonged to polyethylene tube and its holes deformations or the locking screw deformation itself [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…It was stated that the stress on 1-mm deformation was defined as "yielding strength" instead of "true yield point [7-9, 14, 15]. It was concluded that due to the trapping of screws within the tube holes, the diameter of the metal tube hole must be 7 mm in order to clearly determine the true yield point [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations